Life cicle of Xanthogaleruca luteola (Coleoptera: Chrysomelidae) in Santiago, Chile, and sex fenotype differentiation of adults - Huerta, A.=700 1 Chiffelle, I.; Puga, K.; Azua, F.; Jimenez, R.; Araya, J.E.
(Es, En)
Ilus; 28 ref.
Keywords: ULMUS; PYRRHALTA LUTEOLA; COLEOPTERA; INSECTA; CICLO DE VIDA; GENITALIA; ESPAÑA; VAQUITA DEL OLMO; BOLETIN DE SANIDAD VEGETAL: PLAGAS